THE IMPACT OF SOCIAL MEDIA ON CONSUMER BEHAVIOUR: TRENDS, CHALLENGES, AND OPPORTUNITIES - Ayesha, Noor (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social media has fundamentally transformed the landscape of consumer behavior, influencing the way consumers interact with brands, make purchasing decisions, and share information. This study explores the multifaceted impact of social media on consumer behavior, highlighting emerging trends, challenges, and opportunities. It examines how platforms like Facebook, Instagram, Twitter, and TikTok have reshaped consumer engagement, loyalty, and brand perception. The study also addresses the challenges that arise from social media’s influence, such as privacy concerns, misinformation, and the overwhelming abundance of choices. Finally, it outlines potential strategies that businesses can adopt to harness the power of social media in driving consumer behavior effectively. Through a comprehensive analysis, this research provides valuable insights for marketers, businesses, and academics seeking to understand the evolving dynamics of consumer behavior in the digital age.